Antiaging agent MB-S and its preparation method and application
By developing a new anti-aging agent MB-S, the catalytic reaction is used to reduce its melting point and improve its anti-aging ability, the processing difficulty caused by insufficient anti-aging ability and high melting point of the existing anti-aging agent is solved, and higher wear and oxidation resistance is achieved, which extends the life of rubber products and reduces maintenance costs.
Patent Information
- Application Number
- CN202411176243.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing anti-aging agents MB and 4010NA have weak anti-aging capabilities in practical applications, and the melting point of the anti-aging agent MB is relatively high, making it difficult to mix evenly with the substrate, increasing production costs and energy consumption.
A new anti-aging agent MB-S was developed. By catalyzing the anti-aging agent MB, aldehyde compound and hydroxylamine or its inorganic salt in an alcohol solvent, MB-S with a low melting point and strong anti-aging ability was prepared.
MB-S significantly improves the wear resistance and thermal oxygen aging resistance of nitrile rubber. The compressive permanent deformation of vulcanized rubber is minimal. The tensile strength and elongation retention rate after aging are better than the other two anti-aging agents, extending the service life of rubber products and reducing maintenance costs.
Smart Images

Figure CN119060069B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber antioxidants, and specifically relates to an antioxidant MB-S and a preparation method and application thereof. Background Art
[0002] Rubber materials are widely used in many fields such as life, industry and military, but most rubbers are unsaturated rubbers. The large number of carbon-carbon double bonds in the rubber structure makes it very easy to age, and aging phenomena such as softening, stickiness, hardening, brittleness, cracking, and loss of gloss appear. For the problems caused by rubber aging, adding antioxidants is considered to be the most convenient way to delay aging, because this method does not change the processing technology of rubber. Antioxidant 4010NA is a commonly used high-efficiency antioxidant, widely used in natural rubber, nitrile rubber and other rubbers. It has excellent protective effect against flexural fatigue caused by ozone, wind erosion and mechanical stress, and also has significant protective effect against oxygen, heat, high-energy radiation, etc. It has no effect on vulcanization and has good dispersibility. It can be used to manufacture aircraft and automobile tires, cables and other industrial rubber products. It is suitable for dark natural rubber and synthetic rubber products. It can be used for tire carcasses, belts and other rubber products, and can be used together with antioxidant RD to enhance its antioxidant properties. Antioxidant MB, also known as 2-mercaptobenzimidazole, is widely used in the rubber industry and related fields. The following are the structural formulas of antioxidant MB and antioxidant 4010NA:
[0003]
[0004] However, in actual application, antioxidant MB and antioxidant 4010NA have weak anti-aging ability. In addition, antioxidant MB has a high melting point. Antioxidants with high melting points are more difficult to mix evenly with the base material during the processing of rubber or plastic, which may require higher processing temperatures or longer processing times, thereby increasing production costs and energy consumption. Summary of the invention
[0005] The invention provides an antioxidant MB-S and a preparation method and application thereof. The antioxidant MB-S has strong anti-aging ability, helps to improve the service life and performance stability of rubber products, and reduces maintenance costs.
[0006] The technical solution of the present invention is:
[0007] In the first aspect, an antioxidant MB-S is disclosed, the name of which is 3,4-dihydro-2H-benzo[4,5]imidazo[2,1-b][1,3,5]thiadiazepine cyclohexane-3-ol, and has the following structural formula:
[0008]
[0009] In a second aspect, a method for preparing the antioxidant MB-S is disclosed. The antioxidant MB-S is synthesized using antioxidant MB, aldehyde compounds and hydroxylamine or its inorganic salt as raw materials in an alcohol solvent under the catalytic action of a catalyst, and specifically comprises the following steps:
[0010] 1) placing antioxidant MB and aldehyde compounds in an alcohol solvent, adding a catalyst, and reacting under reflux for 2-6 hours to generate an intermediate dihydroxymethylated MB;
[0011] 2) Add hydroxylamine or its inorganic salt, continue the reflux reaction for 2-6 hours, add alkaline solution to neutralize the pH to 6-7, cool and crystallize, centrifuge, and dry to obtain antioxidant MB-S.
[0012] Preferably, the alcohol solvent is one of methanol, ethanol, propanol, isopropanol, butanol and octanol.
[0013] Preferably, the aldehyde compound is one of paraformaldehyde, trioxymethylene and formaldehyde solution.
[0014] Preferably, the inorganic hydroxylamine salt is hydroxylamine hydrochloride or hydroxylamine sulfate.
[0015] Preferably, the catalyst is one of sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, triethylamine, triethylenediamine or N,N-dibenzylaniline.
[0016] Preferably, the molar ratio of antioxidant MB, aldehyde compound and hydroxylamine or its inorganic salt is 1:(2-4):(0.8-1.2).
[0017] Preferably, the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution and sodium bicarbonate solution.
[0018] Preferably, the amount of the catalyst added is 0.2%-5% of the mass of the antioxidant MB.
[0019] The third aspect discloses the use of the antioxidant MB-S as a rubber antioxidant.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The antioxidant MB-S prepared by the present invention has a significant improvement in the wear resistance of nitrile rubber. In terms of thermal oxidative aging resistance, the compression permanent deformation of the vulcanized rubber with the antioxidant MB-S is minimal, and the retention rate of tensile strength and elongation at break of the vulcanized rubber with the antioxidant MB-S after aging is significantly better than that of the vulcanized rubber with the other two antioxidants. The order of the anti-aging ability of the three antioxidants in rubber is MB-S>MB>4010NA. Strong anti-aging ability can extend the service life of rubber products, improve product performance stability, and reduce maintenance costs.
[0022] 2. The melting point of the antioxidant MB-S of the present invention is 106°C, compared with the melting point of the antioxidant MB of 304°C and the melting point of the antioxidant 4010NA of 76°C. The melting point of MB-S is moderate, and it has good processing performance and storage stability. MB-S has a lower melting point than the antioxidant MB. Antioxidants with high melting points are more difficult to mix evenly with the substrate during the processing of rubber or plastic, which may require higher processing temperatures or longer processing times, thereby increasing production costs and energy consumption; MB-S has a slightly higher melting point than the antioxidant 4010NA. Antioxidants with too low melting points are easy to melt or soften at room temperature or slightly higher temperatures, which brings inconvenience to storage and transportation. This may cause product agglomeration, adhesion or leakage, affecting the use effect of the product; in some occasions that require higher temperature processing or use, antioxidants with too low melting points may have begun to decompose or fail during the processing process, and cannot play their due antioxidant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a Fourier infrared spectrum test chart of MB-S of the present invention.
[0024] Figure 2 It is a schematic diagram of the nuclear magnetic structure of MB-S of the present invention.
[0025] Figure 3 Schematic diagram of transition state structure: (a) transition state of chemical reaction of antioxidant MB-S; (b) transition state of chemical reaction of antioxidant MB; (c) transition state of chemical reaction of antioxidant 4010NA.
[0026] Figure 4 are the vulcanization curves of different nitrile rubber composites.
[0027] Figure 5 is the Shore hardness of different nitrile rubber composites.
[0028] Figure 6 is the wear volume of different nitrile rubber composites.
[0029] Figure 7 is the compression set of different nitrile rubber composites.
[0030] Figure 8 is the stress-strain curve of different nitrile rubber composites.
[0031] Fig. 9 is the tensile strength retention rate of different nitrile rubber composites.
[0032] Fig.10 It is the retention rate of elongation at break of different nitrile rubber composites.
[0033] Fig.11 is the storage modulus of different nitrile rubber composites.
[0034] Fig.12 is the loss modulus of different nitrile rubber composites.
[0035] Fig.13 is the loss factor of different nitrile rubber composites. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0037] Antioxidant MB was purchased from Shandong Star Chemical Co., Ltd.;
[0038] Antioxidant 4010NA was purchased from Sinopec Nanjing Chemical Industry Co., Ltd.
[0039] Example 1
[0040]
[0041] The preparation method of antioxidant MB-S is as follows:
[0042] In a 500mL four-necked flask, add 0.2mol (30g) antioxidant MB, 0.7mol (21g) paraformaldehyde, 1g Na2CO3 and 200mL ethanol, heat to reflux for 4h, cool to below 40°C, add 0.2mol (13.9g) hydroxylamine hydrochloride, heat to reflux for 4h, the reflux temperature is 84°C, cool to below 40°C, neutralize with 50% sodium hydroxide solution to pH 6, cool to below 20°C, and filter to obtain 40.5g of white solid powder, which is the target product MB-S.
[0043] The target product MB-S was tested by Fourier transform infrared spectroscopy. Figure 1 As shown in the figure, the following characteristic absorption peaks can be seen: at 3141cm -1The stretching vibration absorption peak of OH appears at 3024cm -1 The CH stretching vibration absorption peak of the benzene ring appears at 750cm -1 The characteristic absorption peak of =CH deformation in the substituted benzene structure is at 2796cm -1 and 2706cm -1 The stretching vibration absorption peak of -CH2 is at 1610cm -1 The stretching vibration absorption peak of C=N is at 1460cm -1 The benzene ring skeleton stretching vibration absorption peak is at 1284cm -1 The CN stretching vibration absorption peak connected to the benzene ring is at 1120cm -1 The CN stretching vibration absorption peak of fat is at 674cm -1 The point is the stretching vibration absorption peak of CS.
[0044] Using CDCL3 as solvent, the MB-S sample was tested by NMR. Figure 2 As shown. In the 1HNMR spectrum: the series of peaks of MB-S at chemical shifts δ7.22ppm, δ7.24ppm, δ7.40ppm, and δ7.57ppm are all generated by aromatic hydrogen protons in MB-S. The peak at δ8.19ppm corresponds to the hydroxyl signal peak connected to the nitrogen atom, and the peaks at δ4.27ppm and δ5.09ppm belong to the two methylene hydrogen signal peaks.
[0045] According to the above analysis, the characterization results of infrared spectrum and nuclear magnetic resonance hydrogen spectrum confirmed that pure MB-S was obtained. The structure of MB-S is as follows:
[0046]
[0047] Oxidation performance analysis of the antioxidant MB-S prepared in Example 1:
[0048] Compare the energy of the transition state of the antioxidant MB-S, MB, and 4010NA to capture the alkane peroxyl radical reaction, such as Figure 3 As shown. The transition state energy of MB-S reacting with alkane peroxyl radicals is 14.6KJ / mol, while the transition state energies of MB and 4010NA reacting with alkane peroxyl radicals are 39.3KJ / mol and 53.7KJ / mol, respectively. The transition state energy of MB-S reacting with free radicals is much smaller than that of MB and 4010NA, indicating that the antioxidant MB-S is more stably combined with alkane peroxyl radicals and has the best antioxidant capacity compared with the other two antioxidants. The order of antioxidant capacity of these three antioxidants is predicted to be MB-S>MB>4010NA.
[0049] The melting point of antioxidant MB is 304°C, the melting point of antioxidant 4010NA is 76°C, and the melting point of antioxidant MB-S is 106°C. Therefore, MB-S has a lower melting point than antioxidant MB.
[0050] Example 2
[0051] The preparation method of antioxidant MB-S is as follows:
[0052] In a 1000mL four-necked flask, add 0.4mol (60g) antioxidant MB, 1.5mol (45g) polyformaldehyde, 2.5g Na2CO3 and 400mL ethanol, heat to reflux for 6h, cool to below 40°C, add 0.4mol (27.8g) hydroxylamine hydrochloride, heat to reflux for 6h, cool to below 40°C, neutralize with 50% sodium hydroxide solution to pH 6, cool to below 20°C, and filter to obtain 81g of white solid powder, which is the target product MB-S.
[0053] Example 3
[0054] The preparation method of antioxidant MB-S is as follows:
[0055] In a 2000mL four-necked bottle, add 1.0mol (150g) antioxidant MB, 3.3mol (100g) polyformaldehyde, 5gNa2CO3 and 1200mL ethanol, heat to reflux for 6h, cool to below 40°C, add 1.0mol (69.5g) hydroxylamine hydrochloride, heat to reflux for 6h, cool to below 40°C, neutralize with 50% sodium hydroxide solution to pH 6, cool to below 20°C, and filter to obtain 187g of white solid powder, which is the target product MB-S.
[0056] Comparative Example 1
[0057] Different from Example 1, the amount of paraformaldehyde added in this comparative example is 12 g (paraformaldehyde is not added in excess), and the other steps are the same as those in the example. Finally, 28 g of white solid powder is obtained by filtration. Since formaldehyde is easily volatile during the depolymerization process, insufficient addition of paraformaldehyde will result in insufficient amount of intermediates, thereby affecting the cyclization reaction in the second step, and the yield is significantly reduced.
[0058] Comparative Example 2
[0059] Unlike Example 1, in this comparative example, no sodium hydroxide solution was added for pH adjustment, and the other steps were the same as those in the example. Finally, 32 g of white solid powder was obtained by filtration. The purpose of neutralization was that the hydrochloric acid formed by the hydrogen chloride of hydroxylamine hydrochloride being absorbed by water needed to be neutralized, which was beneficial to operation and environmental protection requirements. If it was not neutralized, the product and hydrogen chloride would exist in the form of conjugate salts, resulting in a high melting point, which would cause frost on rubber products during use.
[0060] The antioxidant MB-S prepared in Example 1 was used in the synthesis of nitrile rubber composite materials, and compared with the antioxidants MB and 4010NA commonly used in the prior art, performance tests and aging tests were carried out on them, and the aging resistance of rubber products prepared with the three antioxidants was evaluated.
[0061] In order to evaluate the performance of the three antioxidants, various fillers and additives were kept consistent in the synthesis of nitrile rubber composites. The three formulations all had the following components in parts by weight: 100 parts of NBR (nitrile rubber), 1.5 parts of zinc oxide, 5 parts of sulfur, 1 part of stearic acid, 0.5 parts of accelerator DM, 0.5 parts of accelerator D, 0.2 parts of accelerator TMTD, and 40 parts of carbon black N300. Different types of antioxidants were added to the three formulations. Formula 1 added 2 parts of antioxidant MB-S prepared in Example 1 of the present invention, formula 2 added 2 parts of antioxidant MB, and formula 3 added 2 parts of antioxidant 4010NA. Except for the antioxidant MB-S, the above raw materials are all commercially available, as shown in Table 1.
[0062] Table 1
[0063]
[0064] The raw materials in Table 1 were firstly prepared into a rubber mix using a Haake 300 internal mixer and a double-roll open mill. The rubber mix was placed for at least 24 hours before a vulcanization property test was performed. After the positive vulcanization time of the rubber mix was obtained, a flat vulcanizing press was used to prepare vulcanized rubber products of different specifications, wherein the strip-shaped products were used for Akron wear resistance test, the cylindrical products were used for Shore hardness test and compression permanent deformation test, and the dumbbell-shaped products were used for tensile test and dynamic thermomechanical analysis test. The nitrile rubber composite materials (also referred to as "rubber products") prepared using antioxidant MB-S, antioxidant MB and antioxidant 4010NA were antioxidant MB-S / nitrile rubber, B / nitrile rubber, 4010NA / nitrile rubber, respectively.
[0065] The prepared rubber products were subjected to vulcanization properties test, Mooney viscosity test, Mooney scorch test, Shore hardness test, Akron wear test, compression permanent set test, tensile test, dynamic thermomechanical analysis (DMA) test, and the prepared rubber products were subjected to aging test, so as to evaluate the aging resistance of rubber products prepared with the three antioxidants.
[0066] Vulcanization property test: The performance of vulcanized rubber varies greatly with the length of vulcanization time. Vulcanization time is used to characterize the degree of vulcanization of rubber. The selection of vulcanization time determines the performance of vulcanized rubber. According to the standard of GB / T 34685-2017, the vulcanization property test is carried out under the conditions of 150℃×30min.
[0067] Figure 4 The following are the vulcanization curves of rubber products with different antioxidants added: MB-S / nitrile rubber, B / nitrile rubber, 4010NA / nitrile rubber (represented by MB-S, MB and 4010NA in the figure respectively). Table 2 shows the specific vulcanization characteristic parameters, where T10 is the time required to reach 10% of the difference between the lowest torque and the highest torque during the rubber vulcanization process. This period is the initial stage of vulcanization. T90 is the time required to reach 90% of the difference between the lowest torque and the highest torque during the rubber vulcanization process, that is, the positive vulcanization time. Among them, MB-S / nitrile rubber has the fastest positive vulcanization time. L It reflects the creep properties of rubber. L The smaller the value, the better the creep performance. H It reflects the shear modulus and hardness of rubber. H The higher the value, the higher the hardness. Among the three nitrile rubber composite materials, MB / nitrile rubber M L The smallest, its creep performance is the best, MB-S / nitrile rubber M H The largest, its hardness is the largest. Relatively speaking, the M of the three composite materials L The addition of antioxidant increases the distance between rubber molecules, reduces the interaction between rubber molecular chains, reduces the viscosity of the rubber system, and enhances fluidity, thereby reducing torque, and improving the processing performance and mold filling fluidity of the rubber. In summary, compared with the other two antioxidants, the addition of antioxidant MB-S can shorten the time for nitrile rubber composite materials to reach the positive vulcanization, and the rubber reaches the optimal state faster. Reasonable control of the positive vulcanization time can ensure the quality and performance of the product.
[0068] Table 2 Vulcanization parameters of different nitrile rubber composites
[0069]
[0070] Mooney viscosity test: Mooney viscosity reflects the quality of rubber processing performance, molecular weight and distribution range. Rubber with high Mooney viscosity is not easy to mix evenly and extrude, and its molecular weight is high and the distribution range is wide. Rubber with low Mooney viscosity is easy to stick to the roller, and its molecular weight is low and the distribution range is narrow. If the Mooney viscosity is too low, the tensile strength of the product after vulcanization will be low. According to the standard of GB / T1232.1-2000, the experiment is carried out under the conditions of Z100℃1+4, where Z is the rotation viscosity value; 1 is the preheating time of 1min; 4 is the rotation time of 4min; 100℃ is the test temperature of 100℃.
[0071] Mooney scorch test: The scorch of the rubber compound is an early vulcanization phenomenon that occurs during the processing of the rubber compound. Each rubber compound formula has its scorch time (including the operating scorch time and the remaining scorch time). The length of this period of time should be controlled in production. If it is too short, scorch is likely to occur during operation or the rubber compound cannot flow fully during vulcanization, which makes the pattern unclear and affects the quality of the product or even produces waste. If the scorch time is too long, the vulcanization cycle will increase, thereby reducing production efficiency. According to the standard of GB / T 1233-1992, the Mooney scorch test is carried out at 120°C.
[0072] Mooney viscosity reflects the quality of rubber processing performance, molecular weight and distribution range. Rubber with high Mooney viscosity is not easy to mix evenly and extrude, and its molecular weight is high and its distribution range is wide. Rubber with low Mooney viscosity is easy to stick to the roller, and its molecular weight is low and its distribution range is narrow. If the Mooney viscosity is too low, the tensile strength of the product after vulcanization will be low. Table 3 shows the Mooney viscosity and Mooney scorch time of different nitrile rubber composites. Among the three nitrile rubber composites, MB-S / nitrile rubber has the smallest Mooney viscosity, low molecular weight and stronger plasticity. Scorch refers to the phenomenon of early vulcanization of rubber during processing. The scorch time is often used to measure the difficulty of scorching of rubber. The longer the scorch time, the less likely it is to have early vulcanization during the processing. The shorter the scorch time, the more likely it is to have early vulcanization during the processing. Among the three nitrile rubber composites, the scorch time of MB-S / nitrile rubber is 15:10, the longest scorch time, and it is not easy to have early vulcanization during processing. This shows that the addition of antioxidant MB-S has effective anti-scorch performance.
[0073] Table 3 Mooney viscosity and Mooney scorch time of different nitrile rubber composites
[0074]
[0075] Shore hardness test: Hardness is a physical measure of the degree of deformation or puncture resistance of a material under pressure. Hardness can be divided into relative hardness and absolute hardness. Absolute hardness is generally used in the scientific community and is rarely used in production practice. We usually use the hardness system as a relative hardness, and the following methods are commonly used: Shore (also called Shaw), Rockwell, and Brinell. Shaw is generally used on rubber materials. According to the standard of GB / T 2411-2008, the Shore A hardness tester is used for testing.
[0076] Figure 5The Shore hardness of different nitrile rubber composite materials: MB-S / nitrile rubber hardness is 67HA, MB / nitrile rubber hardness is 65HA, and 4010NA / nitrile rubber hardness is 64HA. The hardness of the three nitrile rubber composite materials is very small. Relatively speaking, the hardness of MB-S / nitrile rubber is slightly larger. The addition of antioxidant has little effect on the hardness of the composite material.
[0077] Akron wear test: Akron wear test can test the rolling friction wear resistance of vulcanized rubber. The test is carried out in accordance with the standard of GB / T1689-2014. After the sample is pre-grinded for 15 minutes, the debris is removed and weighed, and its mass is recorded as m1. The pre-grinded sample is tested. After the sample runs 1.6 km on the Akron wear machine, the debris is removed and weighed, and its mass is recorded as m2. The density ρ of the sample is determined in accordance with the national standard GB / T533. According to the standard of GB / T1689-2014, the sample wear volume V is calculated according to formula (1)
[0078]
[0079] The wear volume of the three nitrile rubber composite materials can be calculated according to formula (1). Figure 6 is the wear volume of different nitrile rubber composite materials, the wear volume of MB-S / nitrile rubber is 0.11cm 3 MB / nitrile rubber wear volume is 0.12 cm 3 , 4010NA / nitrile rubber wear volume is 0.21cm 3 . The wear volume refers to the volume of the sample lost due to wear during the wear test. By measuring the mass loss and volume loss of the sample, the wear resistance of the material can be evaluated. The larger the Akron wear volume, the worse the wear resistance of the material. Therefore, MB-S / nitrile rubber has the best wear resistance, which is due to the addition of antioxidant MB-S, which increases the hardness of the composite material. The effect of antioxidant MB-S on the wear resistance of nitrile rubber is better than the other two antioxidants.
[0080] Compression permanent deformation test: The test was conducted in accordance with the national standard GB / T7759.1-2015. The initial height of the sample was measured as h0. The sample was loaded into the mold and placed at 70°C and a compression rate of 25% for 24 hours. After reaching the specified time, the sample was taken out and placed at room temperature for 30 minutes. The height of the sample was measured as h1. According to the standard GB / T7759.1-2015, the compression permanent deformation C was calculated according to formula (2).
[0081]
[0082] Wherein, hS is the height of the stopper, and the height of the stopper is 4.8 mm.
[0083] The compression permanent deformation of the three nitrile rubber composite materials can be calculated according to formula (2). Figure 7 The compression permanent deformation of different nitrile rubber composite materials under 70℃×24h conditions. The compression permanent deformation of MB-S / nitrile rubber is 15.2%, the compression permanent deformation of MB / nitrile rubber is 15.8%, and the compression permanent deformation of 4010NA / nitrile rubber is 16.1%. The addition of antioxidants can better delay the aging rate of the rubber, prevent the reduction of the rubber's rebound elasticity, and also have a smaller compression permanent deformation. Among the three nitrile rubber composite materials, MB-S / nitrile rubber has the smallest compression permanent deformation, followed by MB / nitrile rubber, and 4010NA / nitrile rubber is the worst, so the anti-aging performance of the three antioxidants is MB-S>MB>4010NA.
[0084] Tensile test: The static mechanical properties of nitrile rubber composites were tested using an electric tensile tester. According to the standard GB / T528-2009, dumbbell-shaped specimens were tested at room temperature with a tensile rate of 500 mm / min. In order to evaluate the effect of antioxidants, the retention of tensile strength and elongation at break after aging was determined by calculating the average value of at least five sets of tests for each sample.
[0085] Figure 8 Table 4 shows the tensile strength and elongation at break of different nitrile rubber composite materials before aging. The tensile performance parameters of MB-S / nitrile rubber, MB / nitrile rubber and 4010NA / nitrile rubber composite materials are very close, with tensile strength of 17.9-18.2MPa and elongation at break between 418-442%. From the stress-strain curve, the performance of MB-S / nitrile rubber composite material is better than the other two composite materials. The elongation at break is affected by the molecular weight, aggregate structure and phase structure of the blending system. Because the essence of the tensile deformation process is a process that consumes the ability to change conformation and the flexibility of the polymer chain, the fundamental factors affecting the elongation at break can be attributed to the flexibility and conformational change ability of the molecular chain. The addition of antioxidant isolates the van der Waals force between the rubber molecular chains, and also makes the filler more evenly dispersed, reduces the intermolecular force, and partially releases the state of mutual restraint between the rubber molecular chains. The rubber conformational change is easier, so the flexibility of the rubber molecular chain increases and the elongation at break increases.
[0086] Table 4 Tensile strength and elongation at break of different nitrile rubber composites
[0087]
[0088] Dynamic Mechanical Analysis (DMA): DMA is widely used in characterizing the thermal properties, physical properties, mechanical properties and stability of materials, and has important practical significance for the research and development of materials and quality control in production. According to the standard of GB / T 40396-2021, the test is carried out in the tensile deformation mode at a temperature range of -60 to 100°C and a heating rate of 3°C / min.
[0089] Retention rate of mechanical properties of nitrile rubber composites: In order to investigate the anti-aging ability of the three antioxidants, the three antioxidants were added to nitrile rubber together with other additives and fillers to prepare mixed rubber and vulcanize it, and then the vulcanized rubber was subjected to thermal oxidation aging experiments.
[0090] The aging temperature is 70℃, and the retention rate of the tensile strength and elongation at break of the tested samples after aging for 24h, 36h, and 48h is used as the anti-aging efficiency. The retention rate calculation formula is:
[0091] Retention rate = (performance parameter after aging / performance parameter before aging × 100% (3)
[0092] Table 5 shows the specific parameters of tensile strength parameters and tensile strength retention rate of nitrile rubber of three formulations after aging at 70°C for 24h, 36h and 48h. Fig. 9 This is the relationship curve between the tensile strength retention rate of nitrile rubber vulcanizate and the change of thermal oxidative aging time. After aging for 24 hours, the tensile strengths of the three different vulcanizates, MB-S / nitrile rubber, MB / nitrile rubber and 4010NA / nitrile rubber, were 17.1MPa, 16.7MPa and 17.1MPa respectively, and the tensile strength of MB-S / nitrile rubber was superior among the three; after aging for 36 hours, the tensile strengths were 16.9MPa, 16.2MPa and 15.8MPa respectively, and the tensile strength of MB-S / nitrile rubber was the largest among the three; after aging for 48 hours, the tensile strengths were 16.8MPa, 15.8MPa and 13.1MPa respectively, and the tensile strength of MB-S / nitrile rubber was still higher than the other two. Rubber aging is a complex and comprehensive chemical reaction process. Affected by thermal oxidative aging, the tensile strengths of the three different formula vulcanizates are constantly decreasing with the extension of aging time. However, no matter the aging time is 24h, 36h or 48h, the tensile strength of the vulcanized rubber with the addition of antioxidant MB-S is superior to that of MB / nitrile rubber and 4010NA / nitrile rubber. Especially after aging for 48h, the tensile strength retention rate of MB-S / nitrile rubber can reach 93.8%, while that of MB / styrene-butadiene rubber and 4010NA / styrene-butadiene rubber is 87.7% and 71.9% respectively, indicating that the antioxidant efficiency of MB-S is higher than that of MB and 4010NA. Especially after aging for a long time of 48h, the retention rate is as high as 93.8%, indicating that MB-S has excellent long-term anti-aging effect.
[0093] Table 6 shows the specific parameters of the elongation at break and the retention rate of elongation at break of the three formulations of nitrile rubber after aging at 70°C for 24h, 36h and 48h. Fig.10 This is the relationship curve between the elongation at break retention rate of nitrile rubber vulcanizate and the change of thermal oxidative aging time. When the three different vulcanizates of MB-S / nitrile rubber, MB / nitrile rubber and 4010NA / nitrile rubber are aged for 24 hours, the elongation at break is 368%, 350%, and 393% respectively, and the elongation at break of the three vulcanizates is close; when aged for 36 hours, the elongation at break is 285%, 276%, and 226% respectively, and the elongation at break of MB-S / nitrile rubber is superior among the three; when aged for 48 hours, the elongation at break is 240%, 174%, and 144% respectively, and the elongation at break of MB-S / nitrile rubber is still higher than the other two. Affected by thermal oxidative aging, the elongation at break of the three different formula vulcanizates is constantly decreasing with the extension of aging time. However, during the aging process, the elongation at break retention rate of MB-S / nitrile rubber shows the highest trend among the three different vulcanizates. After aging for 24 hours, the elongation at break of MB-S / nitrile rubber, MB / nitrile rubber and 4010NA / nitrile rubber were retained at 88.0%, 79.2% and 88.3% respectively. After aging for 48 hours, the elongation at break of MB-S / nitrile rubber, MB / nitrile rubber and 4010NA / nitrile rubber were retained at 57.4%, 39.4% and 32.4% respectively. In the early stage of aging, the elongation at break and its retention rate of 4010NA / nitrile rubber were slightly higher than those of the other two vulcanized rubbers, but with the increase of aging time, the elongation at break retention rate of MB-S / nitrile rubber was much higher than that of the other two vulcanized rubbers, indicating that the long-term anti-aging efficiency of MB-S is better than that of the other two antioxidants, and it can effectively slow down the decrease of elongation at break of rubber. Therefore, the antioxidant MB-S has more advantages in the long-term anti-aging process.
[0094] Table 5 Tensile strength and retention rate of NBR vulcanizate after aging for different time periods
[0095]
[0096] Table 6 Elongation at break and retention rate of NBR vulcanizate at different aging times
[0097]
[0098] Storage modulus of nitrile rubber composites: Fig.11The storage modulus E' of nitrile rubber compound changes with temperature. When the temperature is -60℃, the storage modulus E' of MB-S / nitrile rubber is higher, and the storage modulus of MB / nitrile rubber and 4010NA / nitrile rubber are close. As the temperature rises, the storage modulus of the three compounds decreases and eventually tends to 0MPa. The larger the storage modulus, the more energy the material stores when it is deformed, and the stronger its ability to resist deformation. Therefore, MB-S / nitrile rubber has a stronger ability to resist deformation than the other two compounds.
[0099] Loss modulus of nitrile rubber composites: Fig.12 The curve of storage modulus E" of nitrile rubber compound with temperature. At -9.4℃, the loss modulus of the three compounds reached a maximum value of 411.1MPa, among which 4010NA / nitrile rubber had the largest loss modulus, and MB / nitrile rubber and MB-S / nitrile rubber had similar loss moduli. Then, with the increase of temperature, the loss modulus gradually decreased and finally tended to 0MPa. The larger the loss modulus, the greater the energy loss of the material under alternating loads, which reflects the ability of the material to resist energy loss when subjected to repeated stress or strain. Therefore, MB / nitrile rubber and MB-S / nitrile rubber are stronger in resisting energy loss than 4010NA / nitrile rubber.
[0100] Loss factor of nitrile rubber composites: Fig.13 The loss factor tanδ of nitrile rubber compound varies with temperature. Among the three compound rubbers, 4010NA / nitrile rubber has the largest loss factor, reaching a maximum value of 1.129 at 0.58℃, MB-S / nitrile rubber and MB / nitrile rubber reach their maximum values at 2.41℃ and 2.15℃, respectively, which are 1.022 and 1.018. When the loss factor is greater than 1, the vulcanized rubber may exhibit poor mechanical properties and fatigue resistance. With the increase of temperature, the loss factor of MB-S / nitrile rubber tends to 0.09, the loss factor of MB / nitrile rubber tends to 0.11, and the loss factor of 4010NA / nitrile rubber tends to 0.10. The larger the loss factor, the smaller the energy loss of the vulcanized rubber under alternating loads, and the better its anti-fatigue and shock absorption performance. The difference in the loss factors of the three vulcanized rubbers is very small, and their anti-fatigue and shock absorption performance are similar. On the other hand, the smaller the loss factor at 60°C, the smaller the rolling resistance of the rubber. The loss factor of the MB-S / nitrile rubber composite at 60°C is lower than that of the other two nitrile rubber composites, so it has a smaller rolling resistance.
[0101] The hardness of nitrile rubber with antioxidant MB-S is not much different from that of nitrile rubber with antioxidant MB and antioxidant 4010NA. In terms of wear, the effect of antioxidant MB-S on the wear resistance of nitrile rubber is better than that of the other two antioxidants. In terms of storage modulus and loss modulus, MB-S / nitrile rubber and MB / nitrile rubber are better than 4010NA / nitrile rubber, but there is little difference between MB-S / nitrile rubber and MB / nitrile rubber, and the loss factors of the three vulcanized rubbers are very small. Their fatigue resistance and shock absorption properties are similar, but at 60℃, the loss factor of MB-S / nitrile rubber is the smallest and has smaller rolling resistance. In terms of resistance to thermal oxidation aging, the compression permanent deformation of the vulcanized rubber with antioxidant MB-S is the smallest, and the retention rate of tensile strength and elongation at break of the vulcanized rubber with antioxidant MB-S after aging is significantly better than that of the vulcanized rubber with the other two antioxidants. In summary, the order of anti-aging ability of the three antioxidants in rubber is MB-S>MB>4010NA.
[0102] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. An antioxidant MB-S, characterized in that: Has the following structural formula: 。 2. The method for preparing the antioxidant MB-S according to claim 1, characterized in that: Antioxidant MB-S is synthesized from antioxidant MB, aldehyde compounds and hydroxylamine or its inorganic salt as raw materials in an alcohol solvent under the catalytic action of a catalyst, specifically comprising the following steps: 1) The antioxidant MB and the aldehyde compound are placed in an alcohol solvent, a catalyst is added, and the reaction is carried out under reflux for 2-6 hours to generate the intermediate dihydroxymethylated MB; 2) Add hydroxylamine or its inorganic salt, continue reflux reaction for 2-6 hours, add alkaline solution to neutralize the pH to 6-7, cool and crystallize, centrifuge, and dry to obtain antioxidant MB-S; The aldehyde compound is one of paraformaldehyde, trioxymethylene and formaldehyde aqueous solution.
3. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: The alcohol solvent is one of methanol, ethanol, propanol, isopropanol, butanol and octanol.
4. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: The inorganic salt of hydroxylamine is hydroxylamine hydrochloride or hydroxylamine sulfate.
5. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: The catalyst is one of sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, triethylamine, triethylenediamine or N,N-dibenzylaniline.
6. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: The molar ratio of antioxidant MB, aldehyde compound and hydroxylamine or its inorganic salt is 1:(2-4):(0.8-1.2).
7. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: In step 2), the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution and sodium bicarbonate solution.
8. The method for preparing the antioxidant MB-S according to claim 2, characterized in that: The amount of catalyst added is 0.2%-5% of the mass of antioxidant MB.
9. Use of the antioxidant MB-S as claimed in claim 1 as a rubber antioxidant.
Citation Information
Patent Citations
Improved low-melting-point anti-aging agent and preparation method thereof
CN115216111A
Process for scavenging thiols
CN1216527A